2016
DOI: 10.1016/j.bpj.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Pulse EPR Measurements of Intramolecular Distances in a TOPP-Labeled Transmembrane Peptide in Lipids

Abstract: We present the performance of nanometer-range pulse electron paramagnetic resonance distance measurements (pulsed electron-electron double resonance/double electron-electron resonance, PELDOR/DEER) on a transmembrane WALP24 peptide labeled with the semirigid unnatural amino acid 4-(3,3,5,5-tetra-methyl-2,6-dioxo-4-oxylpiperazin-1-yl)-l-phenylglycine (TOPP). Distances reported by the TOPP label are compared to the ones reported by the more standard MTSSL spin label, commonly employed in protein studies. Using h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…However, MTSSL is highly flexible, which leads to broad distance distributions especially in a lipid bilayer . We have recently reported that distances measured with MTSSL in the lipid bilayer can be affected by interactions of the label within the lipid environment . Therefore, interpretation of observed distances based on the MTSSL label is often challenging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MTSSL is highly flexible, which leads to broad distance distributions especially in a lipid bilayer . We have recently reported that distances measured with MTSSL in the lipid bilayer can be affected by interactions of the label within the lipid environment . Therefore, interpretation of observed distances based on the MTSSL label is often challenging.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, interpretation of observed distances based on the MTSSL label is often challenging. For α‐peptides, we introduced the semi‐rigid nitroxide label 4‐(3,3,5,5‐tetramethyl‐2,6‐dioxo‐4‐oxylpiperazin‐1‐yl)‐ d ‐phenylglycine (TOPP) that enables structural investigation of transmembrane α‐peptides in their natural environment . Despite its sterical demand, the label did not show influence on the respective secondary structure and gave sharp distance distributions.…”
Section: Methodsmentioning
confidence: 99%
“…However, MTSSL is highly flexible, which leads to complex distance distributions especially in (Holt and Killian 2010) which can be studied using PDS and SDSL. a Tilting of the helix, b bending of the backbone, c stretching of the lipid acyl chains, d peptide aggregation lipid media (Halbmair et al 2016). Thus, an interpretation of the observed distances delivered by the label is often complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Double electron–electron resonance (DEER) or Pulsed Electron–electron double resonance (PELDOR) can be used to probe distance changes upon changing conditions 5 and single-molecule Förster Resonance Energy Transfer (smFRET) can be used to obtain single molecule dynamics of proteins and other macromolecular assemblies 6 10 . The latter two techniques make use of two labels that are introduced for instance by attaching them to cysteine residues via maleimide 11 or methanethiosulfonate chemistry 12 or introducing them as non-natural amino acids 13 . SmFRET even enables study of protein dynamics in vivo 12 .…”
Section: Introductionmentioning
confidence: 99%